A nasalidade em jogo : estratégias para depreender diferenças entre a escrita e a oralidade através do jogo Batalha Nasal - Barbalho Neta, Jandira Cravo (2018)
This research report had as its starting point the study of an interference of the speech in the writing, marked by the presence of nasalization in the text of students of the 7th of Elementary School II. Nasalization is a phonological process proper to speech, not writing. But in the students' texts the presence of words in which a nasal consonant was inserted in contexts that imply error and collaborate with the lag of writing. In addition, it was found that the 'm' rule for 'p' and 'b' was not yet consolidated and the students demonstrated that they did not develop phonological awareness on the articulation points of such contexts, which would possibly reduce the incidence of errors. The methodology used during this process was that of action research, of quantitative approach, of an interpretive nature. The conceptions of Scliar-Cabral (2003), Cristófaro-Silva (2007), Camera Jr (2008), Cagliari (2009), Bagno (2007) Bisol (2013), Abaurre (2013), Moraes (2013), Bortoni-Ricardo (2013) and Seara, Nunes and Lazzarotto-Volcão (2015) constituted the theoretical reference. After attesting the most favorable contexts for the occurrence of nasalization in students' writing, we developed the game Nasal Battle, an action game with questions on Languages, Sergipe Culture and Entertainment, developed to be used as an object of learning and be replicated by other teachers. The results indicate that, the use of the game as a didactic resource effectively collaborates with the reduction of the writing deviations observed here.